Cross-sectional anatomy of leaf blade and leaf sheath of cogon grass (Imperata cylindrica L.) (Journal of Bio-Science, 2018)
Histology of leaf blade and sheath of cogon grass (Imperata cylindrica L.) Beauv., indicated typical C4 Kranz anatomy. Cells of adaxial epidermis were smaller and bulliform cells were present on the adaxial epidermis. The shape of bulliform cells was bulbous; 3-7 cells were present in a group and 3-5 folds larger than epidermal cells. Three types of vascular bundles in respect of size and structure were extra large, large and small and they were part of leaf blade histology. These three sizes of vascular bundles were arranged in successive manner from midrib to leaf margin. Leaf sheath bundles were of two types: large and small. Extra large bundles were flanked by five small and four large bundles but small bundles were alternate found to be with large typed bundles. Extra large bundles were of typical monocotyledonous type but the large type had reduced xylem elements and the small typed was found to be transformed into treachery elements. Small be bundles occupied half the thickness of the flat portion of leaf blade topped by large bulliform cells of the adaxial epidermis. Extra large and large bundle had been extended to upper and lower epidermis. Kranz mesophyll completely encircled the bundle sheath and radiated out into ground tissue. Midrib was projected in abaxial direction and had a central vascular bundle with large and small bundles on either side of it along the abaxial regions. The midrib vascular bundle was devoid of chlorenchymatous bundle sheath and was of non-Kranz type. Continuous sub-epidermal sclerenchyma girders were noted as adaxial hypodermis. Anatomical traits exhibited an important adaptive defense against draught and saline stress of the plant. Quantitative measurement of various anatomical traits indicated strong variations among them.J. bio-sci. 25: 17-26, 2017